Project Management Recognizes R&D Performance - Luis, Daniel Antonio de (Academy of Management Journal, 1964)
The article explores issues on the measurement of the productivity and performance of professional scientific personnel in the U.S. Various industries in the country have been actively seeking a usable method of determining the productivity of professional scientific personnel. Techniques have been developed and used successfully in measuring the performance of workers in terms of physical units of product, yet there has been no comparable methods for determining the productivity and contribution of professionals engaged in mentally creative work. A discussion is presented about the importance of scientific development in the United States.